Analisis Bibliometrik Penelitian Digital Divide Dalam Konteks Akses Dan Literasi Media Digital - Magfirah Ramadanti; Muliadi Mau; Alem Febri Sonni (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technologies and the increasing global internet penetration have driven significant transformations across various sectors of life, while simultaneously intensifying the phenomenon of the digital divide. This inequality is not only related to limited access to technology, but also involves low levels of digital media literacy that affect individuals’ ability to effectively utilize information. Therefore, this study aims to map the development and scientific structure of digital divide research in the context of digital access and media literacy using a bibliometric approach. The data were obtained from the Scopus database, consisting of 124 scientific documents published between 2015 and 2025. The analysis was conducted using Biblioshiny and VOSviewer to generate visualizations such as keyword density maps, co-occurrence networks, and the distribution of contributions by authors and countries. The results indicate that digital divideresearch is dominated by key themes such as digital divide, internet access, digital literacy, and media literacy, which are conceptually interconnected. In addition, there is a significant growth in publications with an annual growth rate of 28.47%, involving 427 authors with a relatively high level of collaboration. These findings suggest that the issue of the digital divide is gaining increasing global attention and continues to develop dynamically. This study highlights the importance of integrating technological access and digital literacy as a strategic effort to reduce the digital divide in the future